2006
DOI: 10.1007/s11010-006-2385-4
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin increases NMDA receptor subunits 2A and 2B concentrations in rat hippocampus

Abstract: We investigated that the effects of melatonin on N-methyl-D: -aspartat receptor (NMDAR) subunits 2A and 2B concentrations and on markers of oxidative stress in hippocampus of rats treated with melatonin for 4 weeks. Animals were divided into four groups according to their melatonin doses (control group (C), n = 7; 5 mg/kg group (M5), n = 7; 10 mg/kg group (M10), n = 8; 20 mg/kg group (M20), n = 8) and received the melatonin as intraperitoneal injection. After 4 weeks of treatment, electrophoretic examination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In agreement with previous evidence [13][14][15], the present study showed that LTP was reduced in TS mice, and melatonin treatment for 5-6 months completely rescued LTP in the CA1 area in trisomic animals. Consistent with these findings, chronic melatonin treatment has been shown to rescue deficits in hippocampal LTP and spatial memory after intra-hippocampal injection of Ab [30], although the acute application of melatonin directly to mouse and rat hippocampal slices inhibits LTP in the CA1 region [67][68][69].…”
Section: Discussionmentioning
confidence: 70%
“…In agreement with previous evidence [13][14][15], the present study showed that LTP was reduced in TS mice, and melatonin treatment for 5-6 months completely rescued LTP in the CA1 area in trisomic animals. Consistent with these findings, chronic melatonin treatment has been shown to rescue deficits in hippocampal LTP and spatial memory after intra-hippocampal injection of Ab [30], although the acute application of melatonin directly to mouse and rat hippocampal slices inhibits LTP in the CA1 region [67][68][69].…”
Section: Discussionmentioning
confidence: 70%
“…There is limited evidence about the mechanisms of action of melatonin in the hippocampus; however, it has been suggested that melatonin might act as a signal gathering hippocampal function through a mechanism involving the activation of NMDA receptors [53][55]. Regardless of the mechanisms involved, there is compelling evidence implicating Mtnr1b (isoform 2 of melatonin receptor) in learning and memory processing.…”
Section: Discussionmentioning
confidence: 99%
“…As long periods of melatonin administration were under the scope of the experience, we chose 5 and 20 mg kg −1 as the lowest and highest doses of treatment. The lack of any side effect and antioxidant property have been reported previously (Sutcu et al ., ; De Butte & Pappas, ; Hemadi et al ., ). According to several previously published research studies, we assumed both doses were specific for melatonin receptors (Oner‐Iyidogan et al ., ; Semercioz et al ., ; Sutcu et al ., ; De Butte & Pappas, ).…”
Section: Methodsmentioning
confidence: 99%